Effects of deep frying on proximate composition and micronutrient of Indian Mackerel (Rastrelliger kanagurta), Eel (Monopterus albus) and Cockle (Anadara granosa) - Rahman, Mohammad Mustafizur; M, Zamri; N, Fadilla (Asian Network for Scientific Information, 2012)
This study was conducted to determine the proximate composition and four micronutrients (Cd, Cu, Mn and Zn) of Indian Mackerel (Rastrelliger kanagurta), Eel (Monopterus albus) and Cockle (Anadara granosa). All fish and shellfish were purchased from local fish market in Kuantan city. All samples of each species were mixed and divided into two groups based on random selection. Each group were again divided into 3 sub-groups, which were considered as replications. The first group were kept uncooked. The second group were fried in a beaker of 400 mL palm cooking oil capacity at a temperature approximately of 180 °C for a 15 minutes period. Both raw and fried samples were analysed following standard methods to determine protein, lipid, ash, moisture, carbohydrate, Cd, Cu, Mn and Zn contents. Results showed that protein content was higher in Indian mackerel and eel than cockle while overall Cd, Cu, Mn and Zn contents were higher in cockle than Indian mackerel and eel. Therefore, fish is better than shellfish in the nutritional point of view. Fried fish and shellfish had very high fat content. Therefore, frying cannot be recommended to prepare a healthy diet. More research is needed including all cooking methods of fish to know the nutritional changes by each cooking method. Fish contains many important fatty acids and amino acids, which might be lost during frying. Therefore, future study should include the effects of different cooking methods on amino acids and fatty acids compositions of fish and shellfish.